ANALISIS SIFAT FISIS DAN MEKANIS BAHAN BIOKERAMIK HYDROXYAPATITE PADAT DARI BAHAN BAKU ALAMI - , DENDY CATUR SETIAWAN, M. K. Herliansyah, ST, MST, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
-